Misrepresentation of Institutional Affiliations: The Results from an Exploratory Case Study of Chilean Authors - Navarrete-Couble, M; Bachelet-Norelli, V; Lizana-Montecinos, F; Uribe, F; Meza-Ducaud, N (Wiley-Blackwell, 2019)
University ranking systems and the publish-or-perish dictum are driving universities and researchers around the world to increase their research productivity and publication outputs. There is no regulated checking of author affiliations as authors are expected to only include affiliations to universities that have contributed substantially to the research conducted and to the published manuscript. Our study aims to establish whether author affiliations can be validated and if there is evidence of misrepresentation from authors who report multiple institutional affiliations. We conducted an exploratory case study on Scopus-indexed articles for 2016, searching all authors who reported multiple institutional affiliations in which at least one of them was to a Chilean university. Of 4,961 author records with multiple affiliations, we were unable to validate 38% of the affiliations to a Chilean university by checking the institutional websites. This affected 40% of articles and was most prevalent in health sciences and for private, new, universities. ORCID identifiers were not suitable for checking affiliations as there was low use of them: only 14% of the multiple-affiliated authors. The inability to validate affiliations might indicate misconduct, and if it is an indication of misrepresentation, it could have profound implications for many stakeholders (universities, journals, ranking houses, funders, and higher education policy-makers) due to inflated publication counts and under-reporting the actual input from individual institutions. © 2019 The Author(s). Learned Publishing © 2019 ALPSP.